All-cause and cause-specific mortality in individuals with zero and minimal coronary artery calcium: A long-term, competing risk analysis in the Coronary Artery Calcium Consortium. (February 2020) - Blaha, Michael J.; Cainzos-Achirica, Miguel; Dardari, Zeina; Blankstein, Ron; Shaw, Leslee J.; Rozanski, Alan; Rumberger, John A.; Dzaye, Omar; Michos, Erin D.; Berman, Daniel S.; Budoff, Matthew J.; Miedema, Michael D.; et al.
Abstract: Background and aims: The long-term associations between zero, minimal coronary artery calcium (CAC) and cause-specific mortality are currently unknown, particularly after accounting for competing risks with other causes of death. Methods: We evaluated 66, 363 individuals from the CAC Consortium (mean age 54 years, 33% women), a multi-center, retrospective cohort study of asymptomatic individuals undergoing CAC scoring for clinical risk assessment. Baseline evaluations occurred between 1991 and 2010. Results: Over a mean of 12 years of follow-up, individuals with CAC = 0 (45% prevalence, mean age 45 years) had stable low rates of coronary heart disease (CHD) death, cardiovascular disease (CVD) death (ranging 0.32 to 0.43 per 1000 person-years), and all-cause death (1.38–1.62 per 1000 person-years). Cancer was the predominant cause of death in this group, yet rates were also very low (0.47–0.79 per 1000 person-years). Compared to CAC = 0, individuals with CAC 1–10 had an increased multivariable-adjusted risk of CVD death only under age 40. Individuals with CAC>10 had multivariable-adjusted increased risks of CHD death, CVD death and all-cause death at all ages, and a higher proportion of CVD deaths. Conclusions: CAC = 0 is a frequent finding among individuals undergoing CAC scanning for risk assessment and is associated with low rates of all-cause death at 12 years of follow-up. Our results support the emerging consensus that CAC = 0 represents a unique population with favorable all-cause prognosis who may be considered for more flexible treatment goals in primary prevention. Detection of any CAC in young adults could be used to trigger aggressive preventive interventions. Graphical abstract: Image 1 Highlights: We evaluated 66, 363 individuals from the Coronary Artery Calcium (CAC) Consortium. CAC = 0 participants had stable low 12-year rates of cardiovascular death. Cancer was the predominant cause of the infrequent deaths in the CAC = 0 group. CAC 1–10 was associated with higher risk of cardiovascular death at ages <40. CAC>10 was associated with higher risk of cardiovascular and all-cause death.